2020
DOI: 10.1007/s00464-020-07900-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the outcomes of index admission laparoscopic cholecystectomy and bile duct exploration for biliary emergencies: a service model

Abstract: Aims The rate of acute laparoscopic cholecystectomy remains low due to operational constraints. The purpose of this study is to evaluate a service model of index admission cholecystectomy with referral protocols, refined logistics and targeted job planning. Methods A prospectively maintained dataset was evaluated to determine the processes of care and outcomes of patients undergoing emergency biliary surgery. The lead author has maintained a 28 years prospective database capturing standard demographic data, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Although the current study had a high workload of biliary emergencies and subsequently a high percentage of difficult cholecystectomies, the morbidity rates for the whole study [ 6 ] were lower than many published studies [ 10 – 16 ]. Laparoscopic CBDEs were also performed in the emergency cohort with a low reintervention rate compared to other studies on CBDE [ 11 18 ] as shown in Table 5 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the current study had a high workload of biliary emergencies and subsequently a high percentage of difficult cholecystectomies, the morbidity rates for the whole study [ 6 ] were lower than many published studies [ 10 – 16 ]. Laparoscopic CBDEs were also performed in the emergency cohort with a low reintervention rate compared to other studies on CBDE [ 11 18 ] as shown in Table 5 .…”
Section: Discussionmentioning
confidence: 91%
“…The objective assessment of operative complexity facilitates audit, research, assessment of training and comparison between studies. The referral pathways and operative techniques have been described in detail in previous studies [5][6][7][8].…”
Section: Methodsmentioning
confidence: 99%
“…Our centre reported its initial experience of urgent cholecystectomy in 2004; at this time, the implementation of a specialist upper GI surgery service led to a reduction in laparoscopic conversion rates from 32 to 12% [ 12 ]. Other centres have reported reducing conversion rates as experience grows and specialisation increases [ 7 , 13 ]. In the CholeS study, the overall open surgery rate was 4.3%, although for emergency cholecystectomy it was 7.4%; these figures are typical of published studies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The referral pathways, operative techniques and postoperative management have been described in the previous studies [7,8]. Emergency admissions with suspected biliary pathology undergo abdominal ultrasound and a plain X-ray of the chest.…”
Section: Methodsmentioning
confidence: 99%